2010
DOI: 10.1177/0363546510372797
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonanatomical Graft Placement in a Series of Failed Anterior Cruciate Ligament Reconstructions

Abstract: The occurrence of nonanatomical graft placement in primary and revision knees may represent an inadequacy of transtibial tunnel drilling techniques to obtain graft placement within the native femoral and tibial footprints. In revision cases, the prior graft location requires close scrutiny so the new graft tunnels are placed at the native anterior cruciate ligament attachments. Independent drilling of tibial and femoral tunnels is recommended using either 2-incision or anteromedial portal techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
112
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 52 publications
4
112
2
6
Order By: Relevance
“…Anatomical ACL graft placement is defined as positioning the ACL femoral and tibial bone tunnels at the centre of the native ACL femoral and tibial attachment sites. Clinical studies have demonstrated that non-anatomical ACL graft placement is the most common technical error leading to recurrent instability following ACL reconstruction [1,2]. ACL reconstruction has been commonly performed using a transtibial technique in which the ACL femoral tunnel is drilled through a tibial tunnel positioned in the posterior half of the native ACL tibial attachment site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical ACL graft placement is defined as positioning the ACL femoral and tibial bone tunnels at the centre of the native ACL femoral and tibial attachment sites. Clinical studies have demonstrated that non-anatomical ACL graft placement is the most common technical error leading to recurrent instability following ACL reconstruction [1,2]. ACL reconstruction has been commonly performed using a transtibial technique in which the ACL femoral tunnel is drilled through a tibial tunnel positioned in the posterior half of the native ACL tibial attachment site.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential problems that can result from drilling the ACL femoral tunnel in hyperflexion include: (1) difficulty passing the endoscopic reamer over the guide pin due to the medial portal tightening in hyperflexion, (2) difficulty visualising the endoscopic reamer due to the reamer dragging the fat pad into the notch and (3) difficulty advancing the endoscopic reamer over the guide wire due to a bend or kink in the guide pin. Drilling the ACL femoral tunnel through a medial portal which is placed too close to the medial femoral condyle can result in iatrogenic injury to the articular cartilage of the medial femoral condyle.…”
mentioning
confidence: 99%
“…1,2 In this regard, it is important to either use an anatomical landmark or go by the remnant of the remaining ACL foot print. Study has shown that determining the correct entry point on the basis of anatomical landmarks is not always accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is unanimous on one point that the incorrect tunnel position is the single most common cause of failure. 1,2 The concept of the anatomical attachment, orientation, and function of the ACL has been a matter of debate for long. Some recent studies have shown that the ACL is attached as a single footprint on the femoral side (the ribbon concept).…”
mentioning
confidence: 99%
“…Due to the unsatisfactory outcomes of conservative treatments for ACL injuries, ACL reconstruction remains the treatment of choice in most young patients who wish to maintain an active lifestyle. However, clinical studies indicate that non-anatomical ACL graft placement is the most common technical error that subsequently leads to recurrent instability after reconstruction [2,3] . Therefore, the anatomical placement of an ACL graft is generally considered critical to the successful clinical outcome of ACL reconstruction [4] , although this topic remains controversial.…”
Section: Introductionmentioning
confidence: 99%